1996
DOI: 10.1088/0964-1726/5/5/014
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of active, passive and hybrid damping in structural design

Abstract: The QUAD4 element found in ASTROS is modified to include piezoelectric layers and a viscoelastic layer. These features are developed and combined to allow for active damping using piezoelectrics, passive damping using constrained layer damping (CLD) and hybrid damping in the form of active constrained layer damping (ACLD). These features are implemented in the QUAD4 element as additional layers in the composite layup definition. The development of these features are presented and the integrity of the implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A uniform electric field is applied to the actuator with will yield a uniform strain that (in the absence of an applied stress) will, by equation one yield a strain: a a a a e E L ε = [11] Given that the field in the actuator is related to the average field in the sensor through a proportional control gain: a s p ave E G E = [12] The boundary condition at the free end for the actuator may be written as:…”
Section: Validation Of Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…A uniform electric field is applied to the actuator with will yield a uniform strain that (in the absence of an applied stress) will, by equation one yield a strain: a a a a e E L ε = [11] Given that the field in the actuator is related to the average field in the sensor through a proportional control gain: a s p ave E G E = [12] The boundary condition at the free end for the actuator may be written as:…”
Section: Validation Of Controlmentioning
confidence: 99%
“…Baz and Ro [10] analyzed the performance of active constrained layer damping (ACLD), where piezoelectric and viscoelastic materials (VEM) were used. Veley and Rao [11] built on these results to make a comparison of active, passive and hybrid damping. Vardan, et al [12] described closed loop finite element modeling of active damping in vibration control.…”
Section: Introductionmentioning
confidence: 99%
“…Fro m d ifferent kinds of control strategies consist of a purely passive control, a purely active control and a hybrid control [5],the use of active control techniques for the suppression of vibrations of very light structures is a very important target in many applications, where the additional masses of stiffeners or dampers should be avoided. Active techniques are also more suitable in cases where the disturbance to be cancelled or the properties of the controlled system vary with time [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of the passive treatment introduces sufficient inherent damping so as to minimize the influence of spillover effects which are liable to degrade or even destabilize mechanical structures under active control. A recent study (Veley and Rao 1996) compared ACLD treatments with purely active and purely passive schemes using both a cantilevered beam and a plate clamped on all four sides. It was shown that the ACLD treatment is superior to active schemes in that desired levels of damping can be introduced with significantly less additional weight.…”
Section: Introductionmentioning
confidence: 99%